SISTEM APLIKASI PENJUALAN DAN PEMBELIAN PADA PANGLONG SINAR GEMILANG JAYA - Suriati, Sri; Agayasa, Ayuni Rezky; Sihombing, Marto; Arliana, Lina (Majalah Ilmiah Kaputama, 2018)
Along with current technological developments, the development of information systems has penetrated in the corporate world which has penetrated them on sales and purchases in a company. Sale and purchase of businesses today mostly still using manual systems.Panglong Sinar Gemilang Jaya is a business that is engaged in the sale and purchase of building materials. This shop is a business that was originally built to meet the needs of local residents for use within the building materials so that local residents do not need to purchase that home away from home.This application systems development, an impact which is very important in getting the information that is accurate and fast. So with this information system is expected to improve performance, and enable consumers to purchase, especially in the long term can be a single proposal that can benefit PanglongSinarGemilang Jaya because it still using manual systems.By using Visual Basic 2010 and MySQL, it can be made an application system sales and purchases.